Behavior of the phase diagrams of Potts model on Cayley tree for order three - Temir, Seyit; Ganikhodjaev, Nasir; Uguz, Selman; Akin, Hasan (Polish Academy of Sciences Publishing House, 2013)
The aim of this paper is to extend the results of Ganikhodjaev et al. to the three state Potts model with competing nearest-neighbor, prolonged next-nearest-neighbor and two-level triple neighbor interactions on a Cayley tree for order 3 and compare with the phase diagrams obtained in Temir et al. and to study modulated phases arising from the frustration effects introduced by nearest-neighbor, prolonged next-nearest-neighbor and two-level triple neighbor interactions.